2014
DOI: 10.1093/bja/aeu052
|View full text |Cite
|
Sign up to set email alerts
|

Can I leave the theatre? A key to more reliable workplace-based assessment

Abstract: Supervisors' judgements on trainee independence with a case, based on the need for direct or more distant supervision, can generate reliable scores of trainee ability without the need for an onerous number of assessments, identify trainees performing below expectations, and track trainee progress towards independent specialist practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 10 publications
3
80
0
2
Order By: Relevance
“…Since 1975, the methodology of Structured Clinical Examinations and Objectives has incorporated a wide variety of activities in very different cases, scenarios and situations, but all of them in simulation conditions, including with the participation of actors, when necessary 41 . This point was emphasized by Weller et al 42 , in 2014, in the article Can I leave the theater? A key to more reliable workplace-based assessments.…”
Section: Salomão Georges Kahwage Neto Et Almentioning
confidence: 93%
“…Since 1975, the methodology of Structured Clinical Examinations and Objectives has incorporated a wide variety of activities in very different cases, scenarios and situations, but all of them in simulation conditions, including with the participation of actors, when necessary 41 . This point was emphasized by Weller et al 42 , in 2014, in the article Can I leave the theater? A key to more reliable workplace-based assessments.…”
Section: Salomão Georges Kahwage Neto Et Almentioning
confidence: 93%
“…Clinical teachers’ perceptions are indeed considered to be a reliable predictor of learners’ difficulties. Weller et al,3 for instance, found that when clinical teachers were asked to identify subjectively which learners required closer supervision, a reliability coefficient of 0.7 was reached with nine observers, whereas 50 observers were required to reach this same coefficient when more traditional measures were used.…”
Section: Resultsmentioning
confidence: 99%
“…Steinert has defined struggling learners as medical trainees who do “not meet the expectations of a training program” 2. Such trainees, who experience more difficulties, often pose an even greater challenge to clinical teachers, since these learners warrant closer supervision,3 which may be time-consuming and compete with time spent on patient care, but may also require specific teaching skills 4. As a result, the supervision of struggling learners has been associated with reactions from clinical teachers ranging from helplessness to frustration and avoidance,2,5 as clinical teachers often perceive that they are ill equipped to supervise these learners efficiently 6…”
Section: Introductionmentioning
confidence: 99%
“…Além da utilização na formação de alunos de graduação em Medicina, o instrumento proposto poderia também ser utilizado em ações de educação médica continuada em vários serviços de saúde, tornando-os presumivelmente mais eficientes e responsáveis sobre a utilização de tecnologias diagnósti-cas, principalmente em países de baixa renda 39 . 42 , em 2014, no artigo intitulado Can I leave the theatre? A key to more reliable workplace-based assessment (Posso abandonar o teatro?…”
Section: Discussionunclassified